PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KARYAWAN TERHADAP KINERJA KARYAWAN (Studi Kasus Pada PT. Bank Tabungan Pensiunan Nasional, Tbk Cabang M.T. Haryono Semarang) - Mohtar Basuki, 04.2502.0043; Lestariningsih, Endang (Students Journal of Accounting and Banking, 2014)
Performance (performance) is the result of the quality and quantity of work achieved by an employee in carrying out their duties in accordance with the responsibilities assigned to him. Factors affecting the achievement of the performance consists of many factors, among which style of leadership, discipline employees. Based on the factors that support the performance of the employees in this study took the title âPengaruh Gaya Kepemimpinan dan Disiplin Karyawan Terhadap Kinerja Karyawan Pada PT. Bank Tabungan Pensiunan Nasional, Tbk Cabang M.T. Haryono Semarangâ(Case Study OnPT. Bank Tabungan Pensiunan Nasional, Tbk Cabang M.T. Haryono Semarang). Analysis of data using qualitative and quantitative analysis which include test validity, reliability testing, multiple regression, the coefficient of determination and test hypotheses include the t test and F test.Keywords: Leadership Style, Work Discipline, employee performance